2021
DOI: 10.3390/ijerph18031203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Growth and Development Check (GDC) on Overweight/Obesity of Children under-5 Years in China: A Propensity Score Analysis

Abstract: To improve health and reduce the rapidly increasing prevalence of overweight and obesity in children, the Chinese government has formulated childcare standards, with the Growth and Development Check (GDC) as the main content. However, few studies have evaluated the impact of the GDC on lowering the risk of childhood overweight and obesity. Using the 2014 China Family Dynamics Survey and propensity score matching (PSM), this article examined the impact of the GDC on overweight/obesity in children aged 5 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…An empirical research confirmed the positive association between the individual psychological trait of hostility and physical health 23 . A research based on the 2014 China Family Dynamics Survey revealed that the subjective awareness of Growth and Development Checks was correlated with the lower risk of childhood overweight/obesity in China 24 . Other researches supported the association between negative emotions and physical health 25 …”
Section: Literature Reviewmentioning
confidence: 78%
See 1 more Smart Citation
“…An empirical research confirmed the positive association between the individual psychological trait of hostility and physical health 23 . A research based on the 2014 China Family Dynamics Survey revealed that the subjective awareness of Growth and Development Checks was correlated with the lower risk of childhood overweight/obesity in China 24 . Other researches supported the association between negative emotions and physical health 25 …”
Section: Literature Reviewmentioning
confidence: 78%
“…23 A research based on the 2014 China Family Dynamics Survey revealed that the subjective awareness of Growth and Development Checks was correlated with the lower risk of childhood overweight/obesity in China. 24 Other researches supported the association between negative emotions and physical health. 25 In general, the analysis of health factors could be divided into the two major interpretive perspectives of individualism and structuralism.…”
Section: Interpretive Perspectives About Residents' Healthmentioning
confidence: 96%